Being targeted: Young women's experience of being identified for a teenage pregnancy prevention programme. (June 2016) - Sorhaindo, Annik; Bonell, Chris; Fletcher, Adam; Jessiman, Patricia; Keogh, Peter; Mitchell, Kirstin
Abstract: Research on the unintended consequences of targeting 'high-risk' young people for health interventions is limited. Using qualitative data from an evaluation of the Teens & Toddlers Pregnancy Prevention programme, we explored how young women experienced being identified as at risk for teenage pregnancy to understand the processes via which unintended consequences may occur. Schools' lack of transparency regarding the targeting strategy and criteria led to feelings of confusion and mistrust among some young women. Black and minority ethnic young women perceived that the assessment of their risk was based on stereotyping. Others felt their outgoing character was misinterpreted as signifying risk. To manage these imposed labels, stigma and reputational risks, young women responded to being targeted by adopting strategies, such as distancing, silence and refusal. To limit harmful consequences, programmes could involve prospective participants in determining their need for intervention or introduce programmes for young people at all levels of risk.